Technology Regeneration Guided with Fibrin Rica in Platelets in Implantodontia - A Literature Review - Gomes Cerqueira, Linda Gabriele; Vanderlei do Amorim, Adriana (European Scientific Journal, ESJ, 2021)
The tissue loss is one of the consequences of damage caused by tooth loss and consequently bone tissue, one of the techniques to minimize or even correct this damage is the use of platelet-rich fibrin-guided tissue regeneration. The use of biomaterials in order to replace bone deficiencies in the regions to be implanted should provide the capacity to regenerate bone tissue, as well as make the new bone structures functional. A bibliographic survey of articles published between 2013 and 2021, articles indexed in the Databases PubMed/MEDLINE, Scielo and Google Scholar, was carried out using the keywords “Fibrin-rich platelets”, "Periodontics", "Connective Tissue" and "Guided Tissue Regeneration". We found 206 articles published in the specified period, after reading the title and abstract, 17 potential articles were identified to be part of the literature review. The technique of using platelet-rich fibrin in dentistry has shown promising results, with low cost, easy execution and accelerated healing process. The limitations of the technique were found the short time to use the material and the small amount obtained after centrifugation.